Identification of a New Variant in NLRP3 Gene by Whole Exome Sequencing in a Patient with Cryopyrin-Associated Periodic Syndrome - Mahdieh Vahedi; Nima Parvaneh; Saeedeh Vahedi; Mohammad Shahrooei; Vahid Ziaee (Case Reports in Immunology)
Background. NLRP3 gene is located in chromosome 1 and encodes a pyrin-like protein. Mutations in this gene are associated with an autoinflammatory disease, called cryopyrin-associated periodic syndrome (CAPS). Case Presentation. We report a 1-year-old boy who had recurrent urticarial rash since birth and joint pain and swelling. He had a missense mutation c.G1060 T (p.A354S) in exon 5 of the NLRP3 gene which was detected by whole exome sequencing. Conclusion. A novel variant was found in the NLRP3 gene which has not been reported by now.